Efficacy of the Video-feedback Intervention to promote Positive Parenting and Sensitive Discipline in Twin Families (VIPP-Twins): Study protocol for a randomized controlled trial. Issue 1 (December 2016) - Euser, Saskia; Bakermans-Kranenburg, Marian; van den Bulk, Bianca; Linting, Mariëlle; Damsteegt, Rani; Vrijhof, Claudia; van Wijk, Ilse; Crone, Eveline; van IJzendoorn, Marinus
Abstract Background Intervention programs with the aim of enhancing parenting quality have been found to be differentially effective in decreasing negative child outcomes such as externalizing behavioral problems, resulting in modest overall effect sizes. Here we present the protocol for a randomized controlled trial to examine the efficacy of the Video-feedback Intervention to promote Positive Parenting and Sensitive Discipline for Twin Families (VIPP-Twins) on parenting quality and children's behavioral control and social competence. In addition, we aim to test the differential susceptibility theory; we examine differential efficacy of the intervention based on genetic make-up or temperament for both parents and children. Lastly, we explore neurobiological mechanisms underlying intervention effects on children's developmental outcomes. Methods/design The original VIPP-SD was adapted for use in families with twins. The VIPP-Twins consists of five biweekly sessions in which the families are visited at home, parent-child interactions are videotaped and parents receive positive feedback on selected video fragments. Families (N = 225) with a same sex twin (mean age = 3.6 years) were recruited to participate in the study. The study consists of four assessments. After two baseline assessments in year 1 and year 2, a random 40 % of the sample will receive the VIPP-Twins program. The first post-test assessment will be carried out one month after the intervention and there will be a long term follow-up assessment two years after the intervention. Measures include observational assessments of parenting and children's social competence and behavioral control, and neurobiological assessments (i.e., hormonal functioning and neural (re-)activity). Discussion Results of the study will provide insights in the efficacy of the VIPP-Twins and reveal moderators and mediators of program efficacy. Overall the randomized controlled trial is an experimental test of the differential susceptibility theory. Trial registration Dutch Trial Register:NTR5312 ; Date registered: July 20, 2015.